Evaluation of the dual role of chlorine dioxide as an antimicrobial agent and defense elicitor against Botrytis cinerea in grapevines - Ramalingam, Srinivasan; Ahn, Soon Young; Myint, Zar Le; Jung, Hee Young; Lee, Seung Yeol; Ryu, Jung A; Lee, Sang-Min; Yun, Hae Keun (Horticulture, environment and biotechnology, 2024)
Chlorine dioxide (ClO2) is a safe, broad-spectrum antimicrobial agent effective against several microorganisms. It exhibits elicitor effects in inducing resistance against plant pathogens, presenting a promising fungicide alternative. This study examined the in vitro antimicrobial and defense elicitor effects of ClO2 against Botrytis cinerea on grapevines. Gene expression and the quality of leaves and berries were evaluated in ‘Kyoho’ grapevines treated with ClO2. ClO2 inhibited B. cinerea spore germination by 75–100%, reduced in vitro vegetative growth by 60% and 25% in PDB and PDA media, respectively, and minimized in vivo infections and disease severity by 30–80% in leaves. Lesion formation in the ClO2-treated berries was reduced by 20–80%. The elevated chlorophyll content and color values revealed the improved vigor in the ClO2-irrigated ‘Kyoho’ grapevines without compromising the fruit quality. The genes associated with antioxidant activity, defense system, and stilbene synthesis were upregulated significantly in grapevine leaves after the ClO2 treatment. In particular, the GPX gene encoding the antioxidant enzyme glutathione peroxidase reached its maximum level, with a log2 value of 12.17 48 hours after the ClO2 treatment. In conclusion, ClO2 has direct antimicrobial potential and induces resistance in grapes against B. cinerea, enhancing vigor without compromising the berry quality. Nevertheless, further research will be needed to address additional parameters before ClO2 can be applied in vineyards to inhibit the incidence of grey mold.